Styrene and Its Derivatives Used in Proton Exchange Membranes and Anion Exchange Membranes for Fuel Cell Applications: A Review - Muhammad Rehman Asghar; Ayesha Zahid; Huaneng Su; Kumar Divya; Muhammad Tuoqeer Anwar; Qian Xu (Batteries)
The proton exchange membrane (PEM) is a critical component of fuel cells, responsible for controlling the flow of protons while minimizing fuel crossover through its channels. The commercial membrane commonly used in fuel cells is made of Nafion, which is expensive and prone to swelling when in contact with water. To address these limitations, various polymers have been explored as alternatives to replace the costly Nafion membrane. Styrene, a versatile and cost-effective material, has emerged as a promising candidate. It can be modified into different forms to meet the requirements of a fuel cell membrane. The aromatic rings in styrene can copolymerize with hydrophilic functional groups, enhancing water (H2O) uptake, proton conductivity, and ion exchange capacity (IEC) of the membrane. Additionally, the hydrophobic nature of styrene helps maintain the structural integrity of the membrane’s channels, reducing excessive swelling and minimizing fuel crossover. The flexible aromatic chains in styrene facilitate the attachment of hydrophilic functional groups, such as sulfonic groups, further improving the membrane’s ion conductivity, IEC, thermal stability, mechanical strength, and oxidative stability. This review article explores the application of styrene and its derivatives in fuel cell membranes, with a focus on proton exchange membrane fuel cells (PEMFCs), direct methanol fuel cells (DMFCs), and anion exchange membrane fuel cells (AEMFCs).